THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN TEACHING - Ruziev Bekhruz (TADQIQOTLAR, 2025)
Abstract: The emergence of artificial intelligence (AI) in education is transforming traditional teaching methods by introducing intelligent systems that personalize learning, support teachers, and increase student engagement. This article explores how AI contributes to modern teaching through personalized content delivery, automated assessment, and intelligent tutoring systems. It also highlights the role of AI in language learning, data-driven decision-making, and reducing teacher workload. While the benefits of AI are numerous, challenges such as data privacy, technological inequality, and the importance of preserving human interaction are discussed. The article concludes that a balanced integration of AI with human-led instruction can enhance educational outcomes and create inclusive learning environments.